Beckman Publishes Brochure on Fast Affinity Chromatography - Eastman, Elke (1985)
The press release discusses Bulletin 5933, devoted to the Ultraffinity-EP column and the fast affinity chromatography (FAC) technique.
Keywords: Marketing; Scientific apparatus and instruments; Chromatographic analysis; Beckman Instruments, Inc.